2006
DOI: 10.1136/pgmj.2006.046565
|View full text |Cite
|
Sign up to set email alerts
|

How to avoid a misdiagnosis in patients presenting with transient loss of consciousness

Abstract: Daily in the UK, frontline medical and paramedical staff are required to manage patients with “collapse?cause”. This universal colloquialism refers to patients who have had an abrupt loss of postural tone. Some of these patients would have had a “blackout” or a transient loss of consciousness (T-LOC). The three most important causes of T-LOC are syncope, epilepsy and psychogenic blackouts. Determining the correct cause is an important challenge; if the initial clinical diagnosis is wrong, investigations may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 87 publications
0
27
0
2
Order By: Relevance
“…The highest prevalence was in the youngest and the oldest patients with a male predominance especially for generalized seizures (figures [12][13][14]. …”
Section: Resultsmentioning
confidence: 99%
“…The highest prevalence was in the youngest and the oldest patients with a male predominance especially for generalized seizures (figures [12][13][14]. …”
Section: Resultsmentioning
confidence: 99%
“…1 Cardiovascular syncope is far more common than epilepsy. 2 Myoclonic jerks are common during cerebral hypoperfusion irrespective of aetiology and are not helpful in discriminating epilepsy from other causes of syncope. 3 This patient had sinus node dysfunction (SND) and its Benoy N Shah, 1 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 This can lead to confusion with epilepsy. 3 Diagnosis of the precise cause of syncope may be difficult, but cardiac causes are more common than epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…4 It has been suggested that a patient with syncope and either preceding faintness or palpitation, an abnormal ECG, a history of structural heart disease, or a family history of sudden cardiac death should be referred initially to a cardiologist for investigation. 1 Both patients were initially referred for neurological investigation, despite both having a significant cardiac history and implanted devices. The correct diagnosis was made by either telemetry or interrogation of the device.…”
Section: Discussionmentioning
confidence: 99%